Manajemen Kesehatan Terpadu: Tinjauan Literatur tentang Pendekatan Efektif untuk Layanan Kesehatan yang Berkualitas dan Berkelanjutan - Robby Prayuda; Eka Fauzihardani; Yulhendri Yulhendri; Rino Rino; Sari Mustika; Ranggi Rahimul Insan; Fahmil Haris (Jurnal Penelitian Pendidikan IPA, 2024)
Health is a fundamental aspect of human life, and providing quality and sustainable healthcare remains a significant challenge globally. With the advancement of medical technology and health information systems, delivering effective, efficient, and affordable healthcare has become increasingly complex. In this context, Integrated Health Management (IHM) has emerged as a promising approach to improving healthcare quality and sustainability. IHM integrates various elements of the healthcare system, such as hospitals, clinics, healthcare professionals, and policies, to achieve more efficient and sustainable health outcomes. This approach aims to address fragmentation in healthcare services, where patients often receive disconnected care without coordination among specialists, medical staff, and institutions. This study conducts a systematic literature review to explore the impact of IHM on healthcare quality and sustainability. Data was gathered from three major academic databases: Scopus, ScienceDirect, and Google Scholar, using keywords such as "Health Management," "Quality Healthcare," and "Sustainable Services." The findings indicate that IHM can significantly enhance healthcare outcomes through the use of digital technologies, decentralization, and community-based models. However, challenges such as limited infrastructure, resistance to change, and financial constraints remain barriers to its widespread implementation. To maximize the effectiveness of IHM, investment in technology, improved governance, and comprehensive training for healthcare professionals are essential. A well-planned, holistic approach is necessary to overcome these challenges and build a sustainable healthcare system